Etika Menuntut Ilmu dalam Kitab Ta’limul Muta’allim dan Relevansinya terhadap Pembentukan Karakter Santri - Mujiati; Apri Eka Budiyono; Ahmad Dawam (CV. Biha Cendekia, 2025)
This study examines the concept of ethics in seeking knowledge in the book Ta'limul Muta'allim by Sheikh Az-Zarnuji and its relevance to the character education of male students at the Darul Ishlah Islamic Boarding School. This study was motivated by the phenomenon of moral decline among the younger generation, characterized by a decline in respect for teachers, weak discipline in learning, and low responsibility among students. Therefore, it is necessary to strengthen classical Islamic ethical values as the foundation for sustainable character building. The research used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews with students, caregivers, and teachers, as well as documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing, with validity ensured through source and technique triangulation. The results of the study show that the concept of ethics in seeking knowledge in the Ta'limul Muta'allim book includes the values of sincere intentions for the sake of Allah, respect for teachers, discipline, sincerity, and consistency in seeking knowledge. These values are applied in an integrated manner at the Darul Ishlah Islamic Boarding School through habituation, exemplary behavior, and boarding school rules. Students are guided in academic, spiritual, and moral aspects. The application of ethical values in seeking knowledge has a positive impact on the character building of students, which is reflected in their religious attitudes, politeness, responsibility, discipline, and high enthusiasm for learning. Thus, the Ta'limul Muta'allim book has strong relevance as a reference for strengthening the character education of students in the modern era.